Artificial insemination in quails through different methods of semen collection (Research, Society and Development, 2020)
The objective of this study was to evaluate different methods of semen collection in quails and the possible viability of artificial insemination. Two collection methods were used: method 1: Abdominal massage in the male, and method 2: Abdominal massage in the female after male copulation. Were used 16 females and 13 males of the species Coturnix coturnix coturnix, aged 10 weeks. In the first method, the selected male was stimulated with the abdominal massage technique to release a foamy secretion through the glands for cloacal and his reproductive apparatus, which was collected in a disposable 1 ml insulin syringe, immediately and disposed in the vagina region of each pair of females in method 1. In the second method 2, the copulation of the selected male was performed in the mannequin females which received an abdominal massage for the removal of the male ejaculate. The eggs of each method were marked and incubated for 18 days. There was a fertility index of 0% in method 1, and 4.88% in method 2. After failure in fertility and feasibility rates, tests for sperm detection were sought in the male reproductive system through histological cuts. The conclusion was that the methods of artificial insemination were not efficient because did not exert the necessary pressure to enable sperm. Thus, the methods of semen collection and artificial insemination applied obtained undesirable indices and are not viable for reproductive management in quails.